THE ANALYSIS OF THE LEARNING PROCESS ON CHOIR EXTRACURRICULAR ACTIVITY AT SENIOR HIGH SCHOOL LEVEL - Rotikan, Geraldo; Kaunang, Meyny; Takalumang, Luccylle (SoCul: International Journal of Research in Social Cultural Issues, 2023)
This study aimed to explore and characterize the extracurricular choir learning activities at SMA Negeri 1 Tondano, with a specific focus on the choir training initiatives implemented to enhance students’ creativity in the realm of music. Employing a descriptive qualitative research approach, this study utilized observation, interviews, and documentation as data collection techniques. The research findings revealed that the teachers employed instructional methods including the demonstration, question-and-answer, and exercise techniques. The teachers in charge of the choir extracurricular implemented various strategies such as planning, execution, and assessment. The choir training process encompassed song material preparation, sheet music analysis, and a structured sequence of activities. This sequence commenced with an opening prayer, followed by warm-up exercises incorporating muscle stretching, breathing drills, and vocal warm-ups. Subsequently, students engaged in the practice of analyzed songs, correcting dynamics, vocals, and articulation, while also applying and fortifying expressions and movements in harmony with the song’s intended message. The session concluded with advice, motivation, and a closing prayer.